2015
DOI: 10.1371/journal.pone.0123442
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms of Interleukin-16 and Risk of Knee Osteoarthritis

Abstract: BackgroundInterleukin-16 (IL-16), a pleiotropic cytokine, plays a fundamental role in inflammatory diseases. This study investigates the association between IL-16 polymorphisms and the risk of knee osteoarthritis (OA) in a Chinese population.MethodsThe IL-16 rs11556218, rs4072111, and rs4778889 polymorphisms were determined in 150 knee OA cases and 147 healthy controls through polymerase chain reaction-restriction fragment length polymorphism.ResultsThe results suggested that the variants in IL-16 gene rs11556… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 43 publications
3
31
1
1
Order By: Relevance
“…In the present study, we selected two common SNPs of IL-16 gene, namely rs4778889, associated with altered levels of gene expression, as well as rs11556218, representing an asparagine to lysine substitution in exon 6 of IL-16 gene [19,29], to explore their potential relevance with the risk of T2DM in a Chinese Han population. Significant differences were detected for rs11556218 polymorphism between T2DM patients group and controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we selected two common SNPs of IL-16 gene, namely rs4778889, associated with altered levels of gene expression, as well as rs11556218, representing an asparagine to lysine substitution in exon 6 of IL-16 gene [19,29], to explore their potential relevance with the risk of T2DM in a Chinese Han population. Significant differences were detected for rs11556218 polymorphism between T2DM patients group and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a significant increase in serum IL-16 has been reported in patients with T2DM, suggesting its potential role in the development of T2DM [18]. Rs4778889 and rs11556218 are the two most-studied SNPs in previous researches, which showed a close association with the onset of several human diseases, such as cancers, osteoarthritis, coronary artery disease [11,19,20]. Furthermore, a remarkably decreased frequency of IL-16 rs4778889 CC genotype has been detected in women with gestational diabetes mellitus (GDM), suggesting the genetic role of IL-16 polymorphisms in GDM [21].…”
Section: Introductionmentioning
confidence: 99%
“…The study by Jiang et al 51 had possible bias because they reported risk estimates only for a rural population. The caseecontrol studies and a hospital-based study by Luo et al 56 may have had considerable selection bias. After serial exclusion of these studies, the combined RR was not significantly changed, but moderate heterogeneity was still present.…”
Section: Smoking and Risk Of Knee Oamentioning
confidence: 99%
“…6I–X). IL-16 has been implicated in the risk for knee OA [94] and OSM expression is associated with OA [95] suggesting that this inflammatory process elicited by MT-COMP may play a role in early joint erosion associated with PSACH. These antioxidant/anti-inflammatory treatments restored chondrocyte proliferation in MT-COMP growth plates, and most importantly, femoral length increased with aspirin or resveratrol treatment compared to the untreated MT-COMP mouse [92].…”
Section: Towards Understanding the Psach Chondrocyte Pathologymentioning
confidence: 99%